KONSTRUKSI SEQUENCING THEORIES PADA ARTIFICIAL INTELLIGENCE (AI) META (TINJAUAN KOMUNIKASI MODEL TURN TAKING THEORY MENURUT HARVEY SACKS) - Usman, Usman; El Hadi, Firdaus; Sartika, Sartika (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
The development of technology helps the means of communication media, one of which is the use of smart phones or gadgets. One of the sophistication that is very much felt is the use of artificial intelligence (AI) Meta on WhatsApp. The use of this AI makes it easier for users to access all the information they need. This study has a research focus on the extent of the use of sequencing theories (conversation sequences) that are often used by AI Meta. The approach to understanding the language style and characteristics of AI itself uses the turn-taking theory technique according to Harvey Sacks, where there are 12 criteria in the sequence of conversations. The methodology of this study is qualitative descriptive through a literature approach that uses the sequence of conversations directly through AI along with its documentation. Based on the results of this study, it can be concluded that of the 12 criteria for the sequence of conversations that took place, only 6 criteria can be responded to well, namely: statement-agreement/disagreement, question-answer, call-answer, closing-closing, request-granting/rejection, accusation-rejection/confession. Through the six criteria of the turn-taking theory, it shows that AI has limitations in communicating, not the same as humans. Meanwhile, the remaining six that cannot be done by AI itself are conversation sequences that are less effective or do not get the response desired by the user.Keywords: Conversation Sequence, Artificial Intelligence (AI), Communication Model